IMPROVING THE METHODOLOGY FOR DEVELOPING THE PHYSICAL QUALITIES OF 14–15-YEAR-OLD VOLLEYBALL PLAYERS - Soliha, Bekzodova (Research Focus International Scientific Journal, 2026)
This article examines the improvement of physical training methods for 14–15- year-old volleyball players. It analyzes age-related physiological and psychological characteristics, identifies key physical qualities required in volleyball, and discusses effective training methods and organization of the training process. The study emphasizes the importance of a systematic and scientifically grounded approach to enhance athletic performance and overall development.